2019
DOI: 10.1002/bjs.11265
|View full text |Cite
|
Sign up to set email alerts
|

Strength of public preferences for endovascular or open aortic aneurysm repair

Abstract: Background This study evaluated public preferences for the treatment processes for abdominal aortic aneurysm repair in order to allow them to be incorporated into a cost‐effectiveness analysis. Methods This was a telephone survey using a trade‐off method in UK resident adults (aged at least 18 years) with no previous diagnosis of a vascular condition. Results Some 167 of 209 participants (79·9 per cent) stated that they would prefer endovascular aneurysm repair (EVAR), 40 (19·1 per cent) preferred open surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…[50] There are a number of methods for obtaining empirical societal valuations through techniques such as discrete choice experiments, [51] time-trade-off, [4] contingent valuation [52] and standard gamble. [53] Such methods have been used to quantify societal preferences for HRQoL and many other aspects of healthcare, including location, [54,55] process utilities, [29,56] waiting times [57,58] and other characteristics of care. [51,59] However, in practice, attributes other than QALYs are considered by advisory committees through a deliberative process within a policy framework.…”
Section: Decision Makingmentioning
confidence: 99%
“…[50] There are a number of methods for obtaining empirical societal valuations through techniques such as discrete choice experiments, [51] time-trade-off, [4] contingent valuation [52] and standard gamble. [53] Such methods have been used to quantify societal preferences for HRQoL and many other aspects of healthcare, including location, [54,55] process utilities, [29,56] waiting times [57,58] and other characteristics of care. [51,59] However, in practice, attributes other than QALYs are considered by advisory committees through a deliberative process within a policy framework.…”
Section: Decision Makingmentioning
confidence: 99%
“…For example, studies have demonstrated that the EQ-5D is insensitive to levels of hearing loss [32] and may not adequately capture the outcome of interventions that affect mental health, [33] dementia [34] or multiple sclerosis. [35] Such measures also fail to include other widely valued aspects of healthcare such as processes of care, [36] compassion, dignity and autonomy. It seems inevitable that rationing decisions based upon evidence that fails to quantify areas such as mental health, disability or compassionate care will result in displacement of healthcare that provides benefits in these domains.…”
Section: Injustices In the Interpretation Of Evidencementioning
confidence: 99%
“…In addition to the health outcomes measured by EQ‐5D™, processes of care may be very important to patients, particularly in relation to interventional procedures where options may include major invasive surgery. It is possible to measure the value that is put on aspects of process, and formally consider trade‐offs against other aspects of outcome.…”
Section: Improving Decision‐makingmentioning
confidence: 99%